Impact of Value-Added Tax on Revenue Generation in Nepal: An ARDL Approach - Kunwar, Keshar Bahadur (Journal of Tikapur Multiple Campus, 2023)
This paper aims to identify the impact of VAT on revenue generation in Nepal using a quantitative method. Testing the unit root of the series is the first step in determining whether the data are stationary. An Augmented Dicky Fuller unit root test and a co-integration test are employed to check the relationship between the variables under study. This study reveals that LNVAT, LNRCE, LNRIT, LNROT, and LNRNT are significant, which is desirable. As a result, a 1 percent increase in value-added tax leads to a 21.60 percent increase in government tax revenue, while a 1 percent increase in custom excise duty leads to a 39.31 percent increase in tax revenue. Other macroeconomic variables such as LNRIT, LNROT, and LNRNT contribute 15.32 percent, 8.51 percent, and 15.06 percent to government revenue generation. The P-value of the Breusch-Godfrey serial correlation LM test, the Breusch-Pagan-Godfrey heteroscedasticity test, and the normalcy test are greater than 5 percent, which is ideal. As a result, there is no autocorrelation or heteroscedasticity in this model. The residual follows a normal distribution. The diagnostic tests show that the models have the expected econometric features and are structurally sound.